Bilateral Use of Iliac Branch Devices for Aortoiliac Aneurysms Is Safe and Feasible, and Procedural Volume Does Not Seem to Affect Technical or Clinical Effectiveness: Early and Midterm Results From the pELVIS International Multicentric Registry. (August 2021) - D'Oria, Mario; Pitoulias, Georgios A.; Torsello, Giovanni F.; Pitoulias, Apostolos G.; Fazzini, Stefano; Masciello, Fabrizio; Verzini, Fabio; Donas, Konstantinos P.; ,
Objective: To evaluate early and follow-up outcomes following bilateral use of iliac branch devices (IBD) for aortoiliac endografting and assess the impact of center volume. We used data from the pELVIS international multicentric registry. Methods: For the purpose of this study, only those patients receiving concomitant bilateral IBD implantation were analyzed. To assess the impact that procedural volume of bilateral IBD implantation could have on early and follow-up outcomes, participating institutions were classified as Site(s) A if they had performed >10 and/or >20% concomitant bilateral IBD procedure, otherwise they were classified as Site(s) B. Endpoints of the analysis included early (ie, 30-day) mortality and morbidity, as well as all-cause and aneurysm-related mortality during follow-up. Additional endpoints that were evaluated included IBD-related reinterventions, IBD occlusion or stenosis requiring reintervention (ie, loss of primary patency), and IBD-related type I endoleak. Results: Overall, 96 patients received bilateral IBD implantation (out of 910 procedures collected in the whole pELVIS cohort), of whom 65 were treated at Site A (ie, Group A) and 31 were treated at Site(s) B (ie, Group B). In total, only 1 death occurred within 30 days from bilateral IBD implantation, and 9 patients experienced at least 1 major complication without any significant difference between subjects in Group A versus those in Group B (10.8% vs 6.5%, p=0.714). In the overall cohort, the 2-year freedom from IBD-related type I endoleaks and IBD primary patency were 96% and 92%, respectively; no significant differences were seen in those rates between Group A or Group B (95% vs 100%, p=0.335; 93% vs 88%, p=0.470). Freedom from any IBD-related reinterventions was 83% at 2 years, with similar rates between study groups (85% vs 83%, p=0.904). Conclusions: Within the pELVIS registry, concomitant bilateral IBD implantation is a safe and feasible technique for management of aortoiliac aneurysms in patients with suitable anatomy. Despite increased technical complexity, effectiveness of the repair is satisfactory with low rates of IBD-related adverse events at mid-term follow-up. Procedural volume does not seem to affect technical or clinical outcomes after bilateral use of IBD, which remains a favorable treatment option in selected patients.